Analisis Kebutuhan Pengembangan Buku Ajar Digital Sejarah untuk Memperkuat Kompetensi Peserta didik Kuliner (Sejarah Kuliner) - Vebrina, Santi; Aisiah, Aisiah (Jurusan Sejarah FIS UNP, 2025)
This research is motivated by the limited learning resources to strengthen the vocational competencies of culinary vocational high school students. The purpose of the research is to analyze the need for the development of digital textbooks for History subjects in vocational high schools specifically for culinary majors. This study applies a mixed method. The research subjects consisted of three history teachers and 21 grade 10 culinary major students at SMK Negeri 3 Padang. Quantitative data were collected through Google Forms and quizzes. Qualitative data were collected through observation and interviews. The results of the study indicate that students' understanding of culinary history is still low. 65% of students do not know culinary history. 58.8% of students need digital open textbooks to strengthen their understanding of culinary history. History teachers also have difficulty finding learning resources about culinary history. On the other hand, the availability of facilities at the school is sufficient to support the use of digital open textbooks. The development of digital culinary history textbooks is essential to create history learning that is contextual, interesting, and appropriate to the vocational work world.